Analisis Logam Berat Pb dan Cd dalam Sampel Ikan dan Kerang secara Spektrofotometri Serapan Atom - Supriatno, Supriatno; Lelifajri, Lelifajri (Jurnal Rekayasa Kimia & Lingkungan, 2009)
The analysis of heavy metals Pb and Cd concentrations in fish and oyster have been carried out by atomic absorption spectrophotometer (AAS) method. The wet digestion method was used for preparation sample prior to AAS detection. Sample was collected from three different location rivers at Lamnyong, Pantee Pirak and Lumbago. The result showed that the Pb and Cd concentration in fish and oyster at difference location were obtained not difference significantly. Pb and Cd contents in fish and oyster were found below lethal concentration. The AAS instrument was still valid to use as the instrument which is obtained of accuration of 0.65% and precise of 0,019 ppm still lower than threshold value of 1% and 0.04 ppm.Keywords: atomic absorbance spektrophootometry, fish, kerang, heavy metal